2016
DOI: 10.1155/2016/7217586
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetic Foot Disease in Patients with Diabetes Mellitus under Renal Replacement Therapy in Lleida, Spain

Abstract: Aim. To assess the prevalence of diabetic foot and other associated conditions in patients with diabetes mellitus under renal replacement in the region of Lleida, Spain. Methods. This was an observational, cross-sectional study of 92 dialysis-treated diabetic patients. Besides a podiatric examination, we explored the presence of cardiovascular risk factors, late diabetes complications, including peripheral neuropathy, atherosclerotic disease, and peripheral artery disease. We assessed risk factors for foot ulc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 29 publications
2
24
1
2
Order By: Relevance
“…The pooled prevalence of diabetic foot ulcers in Africa is 13.0% that is almost the same as Ethiopia [28]. The prevalence of diabetic foot ulcers in this meta-analysis is lower than a study conducted in Khartoum Sudan, 18.1% [29] and Spain 17.4% [30]. This discrepancy could be due to the difference in the study method.…”
Section: Discussioncontrasting
confidence: 67%
“…The pooled prevalence of diabetic foot ulcers in Africa is 13.0% that is almost the same as Ethiopia [28]. The prevalence of diabetic foot ulcers in this meta-analysis is lower than a study conducted in Khartoum Sudan, 18.1% [29] and Spain 17.4% [30]. This discrepancy could be due to the difference in the study method.…”
Section: Discussioncontrasting
confidence: 67%
“…Adults with chronic kidney disease (CKD), particularly those with end-stage renal disease (ESRD) requiring dialysis, have an increased risk of foot ulceration and lower extremity amputation [ 1 5 ]. As a result, dialysis patients have high rates of foot-related hospital admissions [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alex et al,2010 (32) , reported that diabetic cases with hypertension seem to be protected against foot complication as most of patients with hypertension in their sample were on ACE inhibitors (Enalapril), which enhanced peripheral circulation. In contrast, Dòria M et al, 2016 3 , reported that "68.5% of diabetic foot patients had dyslipidaemia, and 84.8% of them had hypertension". Regarding self-care practice for safeguarding against diabetic foot, daily foot wash by soap and warm water and dryness after washing were done by significantly higher control population than cases population .Daily foot inspection for early detection of any trauma or infection was neglected by most of cases and control with no significant in between.…”
Section: Discussionmentioning
confidence: 94%
“…2 Uncontrolled diabetes and peripheral neuropathy were reported as its main risk factors. 3 The diabetic foot may started as simple as minor trauma, impeded toe nail, dryness and inter-digital infections proceeded to ulceration, severe infection, gangrene and amputation. 4 Dealing with preventable risk factors will reduce the cost of hospitalization and management for cases with diabetic foot but this requires first identification of this risk factors and determine it for each patient.…”
Section: Introductionmentioning
confidence: 99%